2019
DOI: 10.1038/s41419-019-1531-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived Ly6C− macrophages promote ischemia-induced chronic kidney disease

Abstract: Macrophages play an important role in renal injury and repair after acute kidney injury (AKI) and the subsequent chronic kidney disease (CKD) that often results. However, as macrophages have a high degree of plasticity and heterogeneity, the function(s) of macrophage subtypes in AKI-to-CKD progression are not fully understood. Here, we focused on Ly6C − macrophages, which are derived from the embryonic yolk sac and post-development become resident in the kidneys. We found that C–C chemok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 51 publications
4
57
0
Order By: Relevance
“…Our research team sorted out Ly6C-macrophages in mice kidney at 5 days after IR operation and injected them under the renal capsule of mice with immune deficiency, finding that the original normal kidney showed damage and intrarenal fibrosis 5 days later, suggesting that Ly6C-macrophages directly damaged kidney and induced subsequent fibrosis [38]. We further identified that Ly6C− macrophages were the dominant intrarenal macrophages after ischemia-reperfusion injury, especially at the chronic phase, and most were derived from the bone marrow and depended on intrarenal CX3CL1-CX3CR1 interaction [38].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…Our research team sorted out Ly6C-macrophages in mice kidney at 5 days after IR operation and injected them under the renal capsule of mice with immune deficiency, finding that the original normal kidney showed damage and intrarenal fibrosis 5 days later, suggesting that Ly6C-macrophages directly damaged kidney and induced subsequent fibrosis [38]. We further identified that Ly6C− macrophages were the dominant intrarenal macrophages after ischemia-reperfusion injury, especially at the chronic phase, and most were derived from the bone marrow and depended on intrarenal CX3CL1-CX3CR1 interaction [38].…”
Section: Lvs Serve As a Bridge Between Innate And Adaptive Immunitymentioning
confidence: 99%
“…Whereas a number of studies have claimed that both CSF-1 and -2 drive M2 skewing of Mϕ in mice with AKI (Zhang et al, 2012; Huen et al, 2015; Wang et al, 2015), it was controversially found that IL-34, another ligand for CSF-1R, does not polarize Mϕ in murine AKI (Baek et al, 2015) and lupus model (Wada et al, 2019), indicating that CSF-1R signaling is dispensable in M2 Mϕ polarization. Supportive of this data, other studies have shown that: (1) increased CSF-1 expression in the resolution phase of AKI is not sufficient to prevent Mϕ from M1 polarization when Mϕ are exposed to an M1 stimulus or when they are deprived of an M2 stimulus during AKI (Fujiu et al, 2011; Susnik et al, 2014; Chiba et al, 2016); (2) quiescent and M2 Mϕ in the resolution phase of AKI differ in transcriptional profiles and functions (Lever et al, 2019; Yang et al, 2019); and (3) the sustained blockage of CSF-1R or the constitutive deletion of CSF-1 ameliorates AKI (Lenda et al, 2003; Ma et al, 2009; more discussion in Assessing M ϕ functions by depleting M ϕ section). Nevertheless, what is consistent throughout all studies (Zhang et al, 2012; Baek et al, 2015; Huen et al, 2015; Wang et al, 2015; Chiba et al, 2016) is that the deficiency in Mϕ survival factors reduces the number of Mϕ (including that of M2 Mϕ predominating in the resolution phase of AKI).…”
Section: Mϕ In Akimentioning
confidence: 77%
“…The migration of Ly6C high monocytes to the site of inflammation occurs through chemotactic mechanisms (e.g., via CCR2 and CX 3 CR1). Therefore, deletion or blockage of chemotaxis receptors on monocytes is found to be protective against ischemia-induced AKI in mice (Furuichi et al, 2003; Li et al, 2008; Lu et al, 2008; Oh et al, 2008; Yang et al, 2019). Monocyte infiltration occurs in the first 48 h (Lu et al, 2008) and completely ceases before day 3 of AKI.…”
Section: Mϕ In Akimentioning
confidence: 99%
See 2 more Smart Citations